Aplikasi Monitoring Air Pada Water Torn Secara Otomatis Berbasis Android dan Di Dukung Oleh Mikrokontroller - Dwiny Meidelfi; Andre Febrian Kasmar; Fanni Sukma; Anggie Meyfrian Pratama (Teknik Elektro Politeknik Negeri Padang, 2020)
Control and monitoring of water in a tank is a computer instrumentation needed in industry. This research discusses a water monitoring application in water torn automatically based on android and supported by a microcontroller. One of the developing technology fields is microcontroller technology. In designing this device, it uses a NodeMCU microcontroller as a data processor and an ultrasonic sensor as data input as well as a buzzer and servo. An ultrasonic sensor is a device that can measure the distance of an object by utilizing reflected ultrasonic waves. This water monitoring uses firebase as a database to store data. To display measurement data, the interface is also designed using the Android Studio application software in the form of graphs, pump status, and water notifications. The test results show that the ultrasonic sensor used is able to measure water levels from 2 cm to 20 cm with an average measurement error of 4.93%. Water monitoring is designed to be able to produce a system output response according to the reference value given. In addition, water level monitoring can be displayed on the Android software interactively